The Economics of Internet Media - Martin Peitz; Markus Reisinger (University of Mannheim, Department of Economics, 2014)
We survey the economics literature on media as it applies to the Internet. The Internet is an important driver behind media convergence and connects information and communication technologies. While new Internet media share some properties with traditional media, several novel features have appeared: On the content side, aggregation by third parties that have no editorial policy and user-generated content have become increasingly important. On the advertiser side, fine-tuned tailoring and targeting of ads based on individual user characteristics are common features on many Internet media and social networks. On the user side, we observe increased possibilities of time-shifting, multi-homing, and active search. These changes have gone hand-in-hand with new players entering media markets, including search engines and Internet service providers. Some of these players face novel strategic considerations, such as how to present search results. In response to these changes, an emerging economics literature focuses on the allocative and welfare implications of this new media landscape. This paper is an attempt to organize these contributions and provide a selective account of novel economic mechanisms that shape market outcomes of Internet media. A large body of work has focused on the advertising part of the industry, while some studies also look at content provision and the interaction between the two.
urn:nbn:de:bsz:180-madoc-371163
Keywords: L82; L86; M37; L13; D21; D22; 330; Internet; media economics; digital media; targeting; news aggregation; search advertising; display advertising; two-sided markets